Does the number of wires used to close a sternotomy have an impact on deep sternal wound infection? - Shaikhrezai, Kasra (Oxford University Press, 2012)
OBJECTIVES: We studied the influence of the number of sternotomy mechanical fixation points on deep sternal wound infection (DSWI). METHODS: Between September 2007 and February 2011, 2672 patients underwent a standard peri-sternal wire closure following a median sternotomy for a first-time cardiac surgery. Data were collected during the study period. RESULTS: The mean age of the patients was 66 ± 11 and 1978 (74.0%) were male. The mean body mass index (BMI) was 28.9 ± 9.3 and the median of the logistic EuroSCORE was 3.14, with a range of 0.88–54.1. Postoperatively, 40 (1.5%) patients developed DSWI after 14 ± 6 days, of whom 39 (92.5%) had positive deep sternal wound specimen cultures, predominantly Staphylococci (62.5%). The risk of DSWI was significantly increased in patients in whom eight or fewer paired points of sternal wire fixation were used when compared with patients in whom nine or more paired points of fixation were used (P = 0.002). Preoperative myocardial infarction (P = 0.001), elevated BMI (P = 0.046), bilateral internal mammary artery harvest (P < 0.0001), postoperative hypoxia (P < 0.0001), sepsis (P = 0.019) and postoperative inotrope use (P = 0.007) significantly increased the risk of DSWI. CONCLUSIONS: DSWI is associated with hypoxia, ischaemia, sepsis and mechanical sternal instability. DSWI may be prevented by using nine or more paired fixation points when closing with standard peri-sternal wires.